Sosialisasi Massage pada Atlet Petanque Sulawesi Selatan - La Kamadi; Ishak Bachtiar; Adam Mappaompo (Universitas Negeri Makassar, 2018)
This socialization program aims to promote massage techniques to athletes and introduce lecturers andstudents works to society. This program aims (1) to socialize the importance of massage for athletes in SouthSulawesi, (2) to find out the enthusiasm and response of petanque athletes in joining the socialization program sothat they realize the importance of pre-match and post-match massage, (3) to find out the athletes understanding inthe socialization. Based on observations during the activity, several positive results were obtained, (1) participantsshowed high enthusiasm. This is due to the fact that there is rarely a socialization related to massage, (2) participantsactively ask questions and share various experiences of injury, (3) participants are also cooperative in taking turnspracticing massage.